2018
DOI: 10.1111/mpp.12688
|View full text |Cite
|
Sign up to set email alerts
|

The population genetic test Tajima's D identifies genes encoding pathogen‐associated molecular patterns and other virulence‐related genes in Ralstonia solanacearum

Abstract: The detection of pathogen-associated molecular patterns (PAMPs) by plant pattern recognition receptors (PRRs) is an essential part of plant immunity. Until recently, elf18, an epitope of elongation factor-Tu (EF-Tu), was the sole confirmed PAMP of Ralstonia solanacearum, the causal agent of bacterial wilt disease, limiting our understanding of R. solanacearum-plant interactions. Therefore, we set out to identify additional R. solanacearum PAMPs based on the hypothesis that genes encoding PAMPs are under select… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 44 publications
0
16
0
Order By: Relevance
“…To compare the previously simulated and observed data based on summary statistics, we used the ape [100] and pegas [101] libraries in R to estimate the number of polymorphic sites and the Tajima's D based on the entire genomes. Tajima's D is commonly used to estimate demographic changes in populations [102,103]. Also, we obtained 1000 sliding windows frames to estimate the Tajima's D along the genomes, as well as the mean and standard deviation of Tajima's D. Tajima's D, π, and Watterson's theta (θw) were estimated for each clade as well as for Sub-clades A, B and G. Since Clades I and VI had three sequences and it was not possible to obtain Tajima's D, we did 1000 replicates in which we subsampled with replacement 10 sequences.…”
Section: Effective Population Size Estimationmentioning
confidence: 99%
“…To compare the previously simulated and observed data based on summary statistics, we used the ape [100] and pegas [101] libraries in R to estimate the number of polymorphic sites and the Tajima's D based on the entire genomes. Tajima's D is commonly used to estimate demographic changes in populations [102,103]. Also, we obtained 1000 sliding windows frames to estimate the Tajima's D along the genomes, as well as the mean and standard deviation of Tajima's D. Tajima's D, π, and Watterson's theta (θw) were estimated for each clade as well as for Sub-clades A, B and G. Since Clades I and VI had three sequences and it was not possible to obtain Tajima's D, we did 1000 replicates in which we subsampled with replacement 10 sequences.…”
Section: Effective Population Size Estimationmentioning
confidence: 99%
“…In silico or experimental evolution is another strategy used to screen pathogenicity genes in R. solanacearum . Forty-nine genes in 37 R. solanacearum genomes were identified as nonneutrally evolving and maybe virulence related using Tajima’s D population genetic test ( 13 ). The multihost experimental evolution of selected independent mutations in the regulatory gene efpR revealed that it is a determinant conditioning host adaptation of R. solanacearum ( 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…To compare the previously simulated and observed data based on summary statistics, we used the ape [98] and pegas [99] libraries in R to estimate the number of polymorphic sites and the Tajima’s D based on the entire genomes. Tajima’s D is commonly used to estimate demographic changes in populations [100, 101]. Also, we obtained 1,000 sliding windows frames to estimate the Tajima’s D along the genomes, as well as the mean and standard deviation of Tajima’s D .…”
Section: Methodsmentioning
confidence: 99%